1997
DOI: 10.1063/1.1147957
|View full text |Cite
|
Sign up to set email alerts
|

The construction of a gas aggregation source for the preparation of mass-selected ultrasmall metal particles

Abstract: Articles you may be interested inInfluence of reactive gas admixture on transition metal cluster nucleation in a gas aggregation cluster sourceThe construction of a gas aggregation source for the preparation of size-selected nanoscale transition metal clusters Rev. Sci. Instrum. 71, 3178 (2000)A design of a nanometer size metal particle generator: Thermal decomposition of metal carbonyls Rev.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 9 publications
0
44
0
Order By: Relevance
“…The resulting directed beam passes through a 6-mm skimmer followed by a high-range/high throughput quadrupole mass filter (Mantis MesoQ, see also (Baker et al 1997)) with a manufacturer stated size resolution of * 2%. The standard mass range of the filter is from 350 amu to * 10 6 amu, but its performance can be extended somewhat to either side of the standard range.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting directed beam passes through a 6-mm skimmer followed by a high-range/high throughput quadrupole mass filter (Mantis MesoQ, see also (Baker et al 1997)) with a manufacturer stated size resolution of * 2%. The standard mass range of the filter is from 350 amu to * 10 6 amu, but its performance can be extended somewhat to either side of the standard range.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12] By alternately depositing clusters and nonmagnetic SiO 2 or C from a second rf sputtering gun onto a Si substrate, the Fe-Pt clusters were effectively isolated from each other to minimize magnetostatic interactions. The composition of the clusters was determined by energy dispersive x-ray spectroscopy ͑EDS͒ in the transmission electron microscope on clusters deposited directly onto carbon support grids.…”
mentioning
confidence: 99%
“…Here, energy products of isotropic magnets reached approximately 20 MGOe. Likewise, cluster formation via gas aggregation [11,12,13] has been used extensively to product nanoscale magnetic particles [14,15,16,17,18,19,20,21]. Rui et al [22] reported, in a preliminary study, on cluster-assembled exchange-spring perma-nent magnets assembled using gas aggregation cluster formation.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of soft and hard magnetic phases, assembled at the nanoscale, results in high remanence and concomitant high-energy products when compared to conventional, non-exchange-coupled permanent magnet materials. For example, isotropic, non-interacting Nd-Fe-B-based magnets have energy products of [12][13][14] MGOe and a theoretical maximum of 16 MGOe [3], while nanocomposite permanent magnets based in the same system have achieved energy products greater than 20 MGOe [4]. However, the magnetic properties critically depend on a uniform, nanoscale soft magnetic phase that enables it to be completely exchange-coupled to the hard magnetic phase.…”
Section: Introductionmentioning
confidence: 99%